2012
DOI: 10.4038/tar.v23i3.4659
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Yield of Hybrid Maize (<i>Zea mays</i> L.) in Relation to Planting Density and Nitrogen Levels during Winter Season in Nepal

Abstract: ABSTRACT. A field experiment was conducted at the National Maize Research Program (NMRP) Farm, Rampur, Chitwan during winter season, 2008/09 to study the effects of three plant densities (55,555, 66,666 and 83,333 plants/ha)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 10 publications
32
46
0
Order By: Relevance
“…An increasing in N dose had advanced in the occurrence of silking by about 3 days during 2012 and 2013. Our results confirms the findings of Dawadi and Sah (2012) who reported that increasing N level decreased the number of days to reach tasseling and silking. Abayomi and Adedoyin (2004) also found that application of higher dose of N significantly reduces time to tassels and silk emergence.…”
Section: Resultssupporting
confidence: 83%
“…An increasing in N dose had advanced in the occurrence of silking by about 3 days during 2012 and 2013. Our results confirms the findings of Dawadi and Sah (2012) who reported that increasing N level decreased the number of days to reach tasseling and silking. Abayomi and Adedoyin (2004) also found that application of higher dose of N significantly reduces time to tassels and silk emergence.…”
Section: Resultssupporting
confidence: 83%
“…Improvement in plant height with each successive increment of nitrogen might be attributed to the fact that nitrogen is an integral part of proteins, the building blocks of plant and it also helps in maintaining higher auxin level which might have resulted in better plant height. Similar findings were reported by Dawadi and Sah (2012) and Nsanzabaganwa et al, (2014).…”
Section: Plant Heightsupporting
confidence: 81%
“…Less plant population and poor nutrient management practices are the major yield reducing factors in maize (Dawadi and Sah, 2012). Nitrogen fertilizer is universally accepted as a key component to high yield and optimum economic return as it plays very important part in crop productivity and its deficiency is one of the major yield limiting factors for cereal production.…”
Section: Introductionmentioning
confidence: 99%